Synthesis of a Biological‐Based Glycoluril with Phosphorous Acid Tags as a New Nanostructured Catalyst: Application for the Synthesis of Novel Natural Henna‐Based Compounds. Issue 11 (24th March 2018) - Moradi, Saeid; Zolfigol, Mohammad A.; Zarei, Mahmoud; Alonso, Diego A.; Khoshnood, Abbas
Abstract: A convenient multicomponent reaction towards the synthesis of natural henna‐based 3‐methyl‐1, 4‐diphenyl‐1, 4‐dihydrobenzo[6,  7]chromeno[2,  3‐ c ]pyrazole‐5, 10‐dione derivatives by using a crabby nano glycoluril tetrakis(methylene phosphorous acid) (GTMPA), as an efficient and recyclable catalyst, under neat conditions is described. The major advantages of the synthetic methodology herein described are high yields, short reaction times, and the reusability of the catalyst, which has been fully characterized by Fourier Transform Infrared Spectroscopy (FT‐IR), Solid Phosphorus Nuclear Magnetic Resonance ( 31 P NMR), Mass spectra (MS), X‐Ray Diffraction (XRD), High Resolution Transmission Electron Microscopy (HRTEM), Scanning Electron Microscope (SEM‐Mapp.), Energy Dispersive X‐Ray (EDX), Thermo Gravimetric Analysis (TGA), Differential Thermal Analysis (DTG), Differential Thermal Analysis (DTA) and X‐Ray Photoelectron Spectroscopy (XPS). The described biological‐based glycoluril with phosphorous acid pending may be applicable for the synthesis of gels, gelators, self‐healing and smart hydrogels. Abstract : A convenient multicomponent reaction towards the synthesis of natural henna‐based 3‐methyl‐1, 4‐diphenyl‐1, 4‐dihydrobenzo[6,  7]chromeno[2,  3‐c]pyrazole‐5, 10‐dione derivatives by using a crabby nano glycoluril tetrakis(methylene phosphorous acid) (GTMPA), as an efficient and recyclable catalyst, under neat conditions is described.